NURSING APPROACH TO PROVIDING PSYCHOLOGICAL SUPPORT FOR SERIOUSLY ILL PATIENTS. (International journal of artificial intelligence, 2025)
This article examines the nursing approach to providing psychological support for seriously ill patients. It highlights the importance of empathy, effective communication, and emotional stability in nursing practice. The study explores how nurses can help patients cope with fear, anxiety, and depression caused by severe illness. It also discusses the principles of therapeutic communication, ethical responsibility, and the creation of a supportive environment. Special attention is given to strategies that enhance the patient’s psychological resilience and improve their overall quality of life. The article emphasizes that psychological support is an integral part of holistic nursing care and plays a vital role in the recovery and well-being of patients.